Penilaian Kualitas Hidup Pasien Post CPR : Studi Literatur - Arista Maisyaroh; Eko Prasetya Widianto; Syaifuddin Kurnianto; Ajheng Gusti Ayu Putri Santoso (Fakultas Ilmu Kesehatan, 2022)
Improving the quality of life of post-CPR (Cardiopulmonary resuscitation) patients can be judged from the results of the outcomes, namely the return of spontaneous circulation and the success of being discharged from the hospital. The research method stirred up the literature review using the Joana Briggs Institute's exclusionary criteria. Five databases with high and medium-quality standards, namely Springer Link, Science Direct, Plos One, Pubmed, and Proquest for the 2017-2022 article, were selected by Prisma 2020 flow chart for systematic review. A total of 10 articles were established in the study. The factor that improves patients' quality of life after CPR is the results of the patient's neurological quality assessment; the better the results of the patient's neurological quality assessment, the more life expectancy by more than five years. Through the results of this literature review, it is hoped that there will be an increase in attention to cardiac arrest patients, not only assessing the success of post-CPR but also must continue to be controlled using instruments, namely ROSC, STD, SF-12, GOS, temperature management, CPC SCORE, GO-FAR SCORE, Blood PH, PCO2, HCO3 to improve the quality of life of post-CPR patients.